Influence of molar ratio of Si–H to Si–CH=CH2 on mechanical and optical properties of silicone rubber. (April 2016) - Yin, Yingle; Chen, Xintai; Lu, Jie; Liu, Zuifang; Chen, Xuhuang
High-strength and optically transparent silicone rubber was prepared using vinyl-MQ silicone resin as base gum. Influence of molar ratio of Si–H to Si–Vi (A value) on curing process as well as mechanical and optical properties were studied. The results show that the curing time and curing temperature decreases, while storage modulus after curing increases, as the A value increases. The optimal mechanical and optical properties can be obtained when the A value is 1.8, leading to the formation of an ultraviolet (UV) transparent silicone rubber with tensile strength of 8.03 MPa and UV transmittance up to 95.8% at 350 nm.